Urban-rural income and wage gaps in the Philippines measurement error, unequal endowments, or factor market failure? - Chua, Kendrick Chua (Philippine Review of Economics, 2015)
Income inequality is higher in the Philippines than in most of its Asian neighbors, and spatial inequality accounts for a fairly large share of it. There is little evidence of labor market failure in the Philippines since, when properly measured, wage gaps by skill level are modest. Unequal endowments account for most of the urban-rural income gaps. That is, individual attributes of workers and households explain the majority of the urban-rural gaps, and schooling, skill, and experience are the three individual characteristics that matter most. Provincial variables, like typhoon incidence, government corruption, school crowding, and access to health facilities, matter far less. Workers born in the cities and immigrants to the cities invest more in human capital than do rural workers. However, this paper cannot tell us how much of that is due to better human-capital-building infrastructure supply in the cities and how much is due to higher urban demand for that infrastructure.